Investigating how teacher leadership can be developed among teachers in a rural school Namibia - Shapange, Laban (Rhodes University, Faculty of Education, Department of Education, 2020)
In established democracies, the notion of 'singular' school leadership practised by the principal has been challenged and a more expansive approach to leadership, which includes teacher leadership, is now widely accepted. However, in Namibia, as with many countries on the African continent, the idea of 'singular' school leadership embedded in the position of principal still prevails. Effective leadership is generally accepted as being core to effective school improvement. The evidence from the school improvement literature constantly highlights that productive leaders exercise an indirect influence on a school's ability and potential to improve and enhance the achievement of learners. This influence does not necessarily come from senior managers only, but partly lies in the strength of middle level leaders and teachers. Research has shown that when teachers assume shared leadership in the redesign of the school, mentor their colleagues, engage in problem solving at the school level and provide professional growth opportunities for their colleagues, they can be effective in bringing about positive change. These findings triggered my interest to study the potential of this approach to teacher leadership development in Namibia. In this context, this study investigated how teacher leadership can be developed among the teachers in a combined school in rural Namibia. The study examined both the understanding of the concept and the practices of teacher leadership among the teachers and school management team and also aimed at bringing about transformation in their practice. The study was a qualitative case study, which took an interventionist approach, framed by Cultural Historical Activity Theory as the theoretical and analytical framework. In addition, the study also used Grant's Model of Teacher Leadership as an analytical tool. Eleven teachers and three members of the management team took part in the study as research participants and were selected by means of the purposive sampling method. Data were generated from two different phases. The first phase of the study examined perceptions and practices of leadership, while in the second phase of the study, a series of intervention Change Laboratory Workshops were conducted. Document analysis, observations, focus group interviews and closed-ended questionnaires were used as data gathering tools. The study lasted for a period of six weeks. Data were analysed using inductive and abductive approaches. The main findings of the study revealed that teacher leadership is understood as an ability to influence and inspire both learners and other teachers. Furthermore, although the participants demonstrated an understanding of teacher leadership as a concept, their understanding of teacher leaders' roles was more on classroom management and control of learners. Teacher leadership development was understood as the process of empowering teachers to take-up various roles and delegated functions through school structures such as committees and within the community. The study further revealed a number of cultural-historic contextual tensions that led to constraints of teacher leadership practice in the case study school. For example, school management team members were seen as a barrier to teacher leadership practice and development. Factors such as limited involvement of teachers in decision-making in the school and lack of school-based continuous professional development programmes for teachers emerged as causes that constrained teacher leadership practice and development in the case study school. The Change Laboratory Workshop findings suggested that in the participants' view, the revival of the different school committees would especially make a positive contribution to teacher leadership practice and development at the case study school.
Keywords: Technical education -- South Africa; Vocational education -- South Africa; Educational leadership -- South Africa; Postsecondary education -- South Africa -- Administration